Geographic information in Livy’s work, a state of the art (Circe de clásicos y modernos, 2018)
This paper deals with different interpretations proposed by modern researchers about the geographic information in Livy’s Ab Urbe Condita. The first part is about the contributions made up to the beginning of the 1980s from an anachronistic conception of geography. In the second part, we consider the contributions made since the mid-1980s on and, finally, we propose a possibility for future research.
Keywords: geography; ethnography; rhetoric; Livy; historiography